Cockayne syndrome – A case report - Palanisamy, Prabakaran; Pullabhota, Arunsantosh; Manjaneyadu, Harshavardhana Kurubara; Mutnuru, Phani Chakarvarty (Indian Journal of Case Reports, 2018)
Cockayne syndrome (CS) is a rare multisystem disorder, with autosomal recessive inheritance. It belongs to the family of nucleotide excision repair diseases with clinical features of failure to thrive, neurodevelopmental delay, cutaneous photosensitivity, pigmentary retinopathy, neurosensory hearing loss, dental caries, premature ageing (progeria), and cachectic dwarfism with associated changes in the brain parenchyma. The imaging findings of the brain along with clinical features are helpful in the diagnosis of CS. There is no permanent treatment option for this condition and death usually occurs due to functional disability/infection by the end of the 3rd decade. We would like to highlight the imaging profile (computed tomography and magnetic resonance imaging findings) of this rare syndrome.